Keterlibatan Julius Robert Oppenheimer dalam Manhattan Project dan Upaya Pengendalian Internasional Energi Atom - Hanitianingrum, Fransisca; Ribawati, Eko (Peneliti.net, 2024)
The purpose of this study was to determine the involvement of physicist Julius Robert Oppenheimer in the Manhattan Project and efforts to control international atomic energy. Oppenheimer's life was shaped and driven by his desire to understand physics and his love of America. Oppenheimer's involvement during the Manhattan Project was as a charismatic leader of the laboratory at Los Alamos, with broad intellectual intelligence, amazing speed of thought and responsibility. In addition to being the leader of the laboratory, Oppenheimer was also chairman of the Atomic Energy Commission. He opposed the re-creation of the hydrogen bomb by the United States government with a strong sense of humanity. Oppenheimer's narrative as a tragic hero has become a parable that neatly summarizes the moral and political dilemmas of the nuclear age. Oppenheimer described how the atomic bomb could be used as a “great threat” and a “great hope” for humanity.